2016
DOI: 10.4236/aim.2016.62007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MIC with MBEC Assay for <i>in Vitro</i> Antimicrobial Susceptibility Testing in Biofilm Forming Clinical Bacterial Isolates

Abstract: Context: MIC results can be misleading for treatment of biofilm associated. The Minimum Biofilm Eradication Concentration (MBEC) measures the determination to be made for a biofilm susceptibility to antibiotics. Aims: Assessment of biofilm production and comparison of the MIC and MBEC assays evaluate differences in the antibiotic sensitivity patterns of different clinical bacterial isolates from patients implanted with medical devices. Settings and Design: Random sampling with experimental study at tertiary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 4 publications
1
22
0
2
Order By: Relevance
“…The MBEC was 2–16 times higher than the MIC value was. This agrees with some previous reports, which suggested that bacteria in biofilm communities are 10–1000 times more resistant than in planktonic form (Mah & O'Toole, ; Mulla, Kumar & Rajdev, ). Because of the limited number of antibiotics available for the treatment of resistant bacterial infections, currently available antimicrobial dose optimization is crucial to improving anti‐infective outcome and preventing development of antimicrobial resistant.…”
Section: Discussionsupporting
confidence: 93%
“…The MBEC was 2–16 times higher than the MIC value was. This agrees with some previous reports, which suggested that bacteria in biofilm communities are 10–1000 times more resistant than in planktonic form (Mah & O'Toole, ; Mulla, Kumar & Rajdev, ). Because of the limited number of antibiotics available for the treatment of resistant bacterial infections, currently available antimicrobial dose optimization is crucial to improving anti‐infective outcome and preventing development of antimicrobial resistant.…”
Section: Discussionsupporting
confidence: 93%
“…In order to obtain maximum therapeutic outcomes and reduce antibiotic resistance, it is crucial to optimize the dosage of available antibiotics, and as such, agents for treatment of resistant bacterial infections are limited. Moreover, to achieve therapeutically effective antimicrobials, the application of biofilm-forming bacteria during in vitro susceptibility studies is more effective [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm producing bacteria are responsible for many recurrent infections and difficult to eradicate. They exhibit resistance to antibiotics by various methods such as restricted penetration of antibiotic into biofilms and expression of resistance genes [1]. Most infectious diseases caused by bacteria are known to be regulated by quorum-sensing mechanisms which in turn regulate the pathogenicity [2].…”
Section: Introductionmentioning
confidence: 99%